To simplify the expression 1/2(z+4) -3 (1/4z + 1), we distribute the -3 and simplify each term.
First, distribute -3 to 1/4z and 1:
-3 * 1/4z = -3/4z
-3 * 1 = -3
The expression becomes:
1/2(z+4) -3/4z - 3
To continue simplifying, we can find a common denominator for 1/2 and 3/4. The common denominator is 4:
1/2 = 2/4
So the expression becomes:
2/4(z+4) -3/4z - 3
Combine like terms:
(2/4 - 3/4)z = -1/4z
2/4 * 4 = 8, so 8/4 = 2
2/4 * 4 = 8, so 8/4 = 2
The simplified expression is:
-1/4z + 2 - 3
Which can be further simplified to:
-1/4z -1
subtract 1/2(z+4) -3 (1/4z + 1)
1 answer